Analysis and Design of E-Commerce Adoption as a Form of Digital Marketing for MSMEs: A Literature Review - Amalia F, Endang (AI Society & STMIK Indonesia, 2024)
Information technology is increasingly advanced and developing according to society's needs. Progress and development of information technology occurs in all sectors, especially trade and business. This makes business actors continue to innovate services related to the use of information technology, so that they can be known by the wider community, especially in transactions and buying and selling especially MSMEs. Besides that, the growth of the digital world and the internet, in particular, has opened up new avenues for MSMEs to offer their products and services. Digital marketing is a viable marketing strategy in the current economic climate. This paper was written using a literature review method or literature review with a qualitative approach. Based on the 7 research both international and national, obtained from various sources via Google Scholar and other online media sources from 2020-2023 with the keywords e-commerce adoption and MSME digital marketing. It can be seen that Branding, Social Media, Content and Caption Marketing, E-mail Marketing, Video Marketing, SEO, Web Design, App Development, SEM have have an important role in digital marketing to increase online sales.